Razvoj trdnosti polivinilacetatnega lepilnega spoja pri lepljenju furnirja - Šauperl, Toni (Les (Ljubljana), 2020)
This article presents the development of the shear strength of two polyvinyl acetate (PVAc) adhesives: Mekol D3 and Mekol SPECIAL when bonding veneer depending on pressing time. Besides testing the strength of the adhesive bond after hot pressing, we also investigated the effect of cooling on the final strength of PVAc adhesive bonds. The shear strength development of the PVAc adhesive bond during hot pressing was determined using an Automated Bonding Evaluation System (ABES). The pressing temperature was constant and was 80 °C, while the pressing time was extended from 30 to 300 seconds in 30-second intervals. The effect of cooling on the final strength of the PVAc adhesive bond was determined after cooling time of 5 and 30 seconds, respectively. Based on the investigations, we found that the shear strength of PVAc adhesive bonds increased with the pressing time and approached to a constant value after a certain time. We found significant differences in the strength of adhesive bonds glued with Mekol D3 and Mekol SPECIAL and a statistically significant effect of cooling on the strength of the adhesive bonds.
Keywords: ABES; adhesive bond; furnir; lepilni spoji; PVAc; shear strength; strižna trdnost; temperatura; temperature; veneer